Self, Me, or I? Unravelling the Triumvirate of Selfhood in Pathological Consciousness - Alexander A. Fingelkurts; Andrew A. Fingelkurts (Brain Sciences)
In this conceptual review, we explore how alterations in the configuration and expression of the three core aspects of experiential Selfhood—‘Self,’ ‘Me’, and ‘I’—both reflect and shape an individual’s susceptibility to neuropsychopathology. Drawing on empirical neurophenomenological evidence and theoretical insights, we examine a range of psychiatric and neurological disorders through the lens of the Selfhood triumvirate. Our findings indicate that, despite variations in the expression of Selfhood aspects across different pathologies, their proportional configuration remains remarkably stable in most conditions, with the ‘Self’ aspect consistently dominant, followed by the ‘Me’ aspect, and finally the ‘I’ aspect. This stability suggests a fundamental neurophenomenological hierarchy in Selfhood organization, which seems to be disrupted only in extreme cases such as vegetative (unresponsive) states and also schizophrenia. Ultimately, we propose that all neuropsychopathologies are best understood as disorders of Selfhood, where disruptions in the dynamic balance and configuration of the ‘Self’, ‘Me’, and ‘I’ aspects accompany neurophenomenological manifestations in distinct dysfunctions and pathologies.